Insight into elevated temperature and thin membrane application for high efficiency in polymer electrolyte water electrolysis. (1st May 2021) - Garbe, Steffen; Futter, Jonas; Schmidt, Thomas J.; Gubler, Lorenz
Abstract: We present a study of a liquid water fed polymer electrolyte water electrolyzer (PEWE) at cell temperatures of up to 120 °C using thin membranes of 50 µm thickness. Further, we show that under these conditions conversion efficiency increases by up to 14% at 3 A cm −2 in comparison to today's state of the art (60 °C, 180 μm membrane). Alternatively, an increase of the current density by a factor of 3 at an efficiency of 75% is possible. A detailed voltage loss analysis is provided that helps to understand to which extent the overpotential contributions are reduced. From hydrogen permeation measurements, we determine faradic efficiency and the safety limits of cell operation revealing that operating temperatures higher than 100 °C with thin membranes are not possible at current densities lower than 0.8 A cm −2 due to the safety limit of 2% hydrogen in oxygen in the anode compartment. The decrease in overpotential allows to significantly reduce the energy requirement or to increase the production rate of hydrogen. The results can help to benchmark future efficiency targets and points towards next generation PEWE materials and components to further reduce loss contributions. Graphical abstract: Image, graphical abstract